14k+-8+9=-13

Simple and best practice solution for 14k+-8+9=-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14k+-8+9=-13 equation:


Simplifying
14k + -8 + 9 = -13

Reorder the terms:
-8 + 9 + 14k = -13

Combine like terms: -8 + 9 = 1
1 + 14k = -13

Solving
1 + 14k = -13

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 14k = -13 + -1

Combine like terms: 1 + -1 = 0
0 + 14k = -13 + -1
14k = -13 + -1

Combine like terms: -13 + -1 = -14
14k = -14

Divide each side by '14'.
k = -1

Simplifying
k = -1

See similar equations:

| (2x+2)30=(2x+4)27 | | 9x+4-2x=3(x+8) | | 2-3x=38 | | 3y*9y^2= | | (10+3+2x)10=(9+3x)9 | | 11x-104=2x-5 | | 4x-3+5x=25 | | 20*8x+0.2*1000=40*8x | | 0=x^2+8x+14 | | (3x-35)+(5x-25)=180 | | 124=6x+d | | 2(x-4)=x+-12+2x | | 124=6x+4 | | 0=-16t^2+380 | | -2y+1=17 | | xy*3x= | | (X+3)6=(x+1)7 | | 8p*2p-7=32 | | y=-16t^2+380 | | 33x+x^2-370=0 | | 13-3x=4(y-2) | | (9+x)9=15(15) | | r*(7+10)=24 | | 5y-2-[6-(3-y)]=4(y-3)+7 | | 18x=9(20) | | (8+2+x)8=(9+x-1)9 | | 5p*3=10 | | 9+7x+x=38 | | 8-3(p-5)=2x+6 | | 55=10+5ln(3x+1) | | 3x+4+2x=x+12 | | 9x*2= |

Equations solver categories